Ultra-low cycle fatigue life prediction of assembled steel rod energy dissipaters with calibrated ductile fracture models. (15th June 2023) - Zhong, Yun-Long; Li, Guo-Qiang; Xiang, Yang; Wang, Yuan-Zuo
Highlight: Ultra-low cycle fatigue life of steel rod energy dissipaters is accurately predicted. Constitutive model considering strain amplitude effect is incorporated in FE model. Ductile fracture model is calibrated and validated against experiments. Fatigue failure mechanism of steel rod dissipaters is scrutinized. Configuration of steel rod energy dissipater is improved. Key factors in predicting fatigue life of steel rod energy dissipaters are clarified. Abstract: In recent decades, various bar-typed miniature energy dissipaters with buckling restrained mechanisms have been proposed for seismic mitigation of engineering structures. The recently proposed assembled steel rod energy dissipater (ASRED), incorporating equally divided tubes as filler components, have shown plump hysteretic loops and remarkable fatigue performance. For such miniature dissipaters with varied dimensions, its ultra-low-cycle fatigue (ULCF) life is correlated with the geometrical dimensions. However, no research concerning this issue has been found. To enable the fracture prediction of ASREDs under various loading situations, numerical models integrated with the ductile fracture model were established in this paper. A newly proposed constitutive model and the famous combined hardening model were both employed in the numerical models to comparatively investigate the key factors affecting the accuracy of the fracture prediction. Moreover, the possible influence of Lode angle was also investigated by employing two different ductile fracture models, namely, the cyclic Bai-Wierzbicki model (CBWM) and the cyclic void growth model (CVGM). Seven specimens with different lengths and loading protocols were simulated, and the results show that the strain amplitude distributes unevenly in the ASRED and increases cycle by cycle at the fixed ends, which leads to the necking-induced failure mode. Using the fracture model of CBWM, numerical simulations that considers the influence of strain amplitude could successfully predict the fracture of all specimens. The dissipaters behaved approximately in an axially loaded state throughout the entire fatigue life, therefore the influence of the Lode angle was negligible, and the fracture predictions given by the CVGM are same with that by the CBWM. Based on a comprehensive analysis of the extended numerical investigations, an improved configuration for ASRED is proposed.